Quantitative systems pharmacology model‐based investigation of adverse gastrointestinal events associated with prolonged treatment with PI3‐kinase inhibitors. (13th December 2021) - Gadkar, Kapil; Friedrich, Christina; Hurez, Vincent; Ruiz, Maria‐Luisa; Dickmann, Leslie; Kumar Jolly, Mohit; Schutt, Leah; Jin, Jin; Ware, Joseph A.; Ramanujan, Saroja
Abstract: Several PI3K inhibitors are in clinical development for the treatment of various forms of cancers, including pan‐PI3K inhibitors targeting all four PI3K isoforms (α, β, γ, and δ), and isoform‐selective inhibitors. Diarrhea and immune‐mediated colitis are among the adverse events observed with PI3K inhibition which limits the maximal tolerated dose. A quantitative systems pharmacology model was developed to investigate PI3K‐inhibitor‐induced colitis. The effects of individual PI3K isoforms on relevant cellular pathways were incorporated into a mechanistic representation of mucosal inflammation. A virtual clinical population captures the observed clinical variability in the onset timing and rates of diarrhea and colitis for seven clinically tested PI3K inhibitors. Model‐based analysis suggests that colitis development is governed by both the inhibition of PI3Kδ, which drives T cell differentiation and proliferation, and PI3Kα, which regulates epithelial barrier integrity. Specifically, when PI3Kα is inhibited below a given threshold, epithelial barrier dysfunction precipitates an exaggerated T effector response due to PI3Kδ‐inhibition, leading to risk of diarrhea and colitis. This synergy explains why the lowest diarrhea and colitis rates are seen with the weakest PI3Kδ inhibition (alpelisib), and higher rates are seen with strong PI3Kδ inhibition if PI3Kα is even mildly inhibited (e.g., idelalisib), whereas strong PI3Kδ inhibition in the absence of PI3Kα inhibition does not result in high colitis rates (umbralisib). Thus, the model‐based analysis suggests that PI3Kα and δ inhibition play unique but synergistic roles in driving colitis. Finally, we explore if and how dose‐regimen might influence colitis rates for molecules that inhibit both PI3Kα and PI3Kδ.